Penalties And Liquidated Damages In A Changing World: Rethinking The Common Law Position - Odetola, Oluwadamilola (Journal of Sustainable Development Law and Policy, 2025)
Why did Antonio agree to give Shylock a pound of his flesh in the Merchant of Venice? Why was Shylock unable to get his pound of flesh? Parties to a contract are allowed to determine their obligations but cannot freely determine the consequences of breach in the event of nonperformance. Such is the paradox in the law of obligations. Virtually every modern contract contains a liquidated damages clause and common law jurisdictions strive to ensure that such clauses do not offend the rule against penalties. This paper examines the principle of contractual freedom within the narrower context of liquidated damages and penalty clauses. It revisits the principles of the law of penalties as expounded in the classic case of Dunlop Pneumatic Tyre Co. Ltd v. New Garage & Motor Co. Ltd, and considers how well they have fared after a century. In making this evaluation, particular attention is paid to English, Australian and Nigerian law. There are issues thrown up by the rigid dichotomy between liquidated damages and penalties and the extent to which commercial partners can negotiate around them. As commercial contracts become more complex and multi-jurisdictional, clarity, certainty and security of transactions have become more fundamental to commercial dealings. This article finds that the dichotomy between penalty and liquidated damages has not only become irrelevant, it also undermines these fundamentals. Arguments made in favour of the dichotomy are self-defeating and confusing. Judicial attempts to bring the penalty rule in consonance with commercial realities also come with problems of their own. Therefore, an abolition of the dichotomy is advocated. This article proposes that in place of the existing unjustifiable paternalistic approach, all agreed damages should be prima facie valid, subject to clear cases of unequal bargaining power and economic oppression.